Working Class Writing and publishing in the Late-Twentieth Century : literature, culture and community - Woodin, Tom (Manchester University Press, 2018)
From the early 1970s, working class writing and publishing in local communities rapidly proliferated into a national movement. This book is the first full evaluation of these developments and opens up new perspectives on literature, culture, class and identity over the past 50 years. Its origins are traced in the context of international shifts in class politics, civil rights, personal expression and cultural change. The writing of young people, older people, adult literacy groups as well as writing workshops is analysed. Thematic chapters explore how audiences consumed this work, the learning of writers, the fierce debates over identity, class and organisation, as well as changing relations with mainstream institutions. The book is accessibly written but engages with a wide range of scholarly work in history, education, cultural studies, literature and sociology. It will be of interest to lecturers and students in these areas as well as the general reader.